Manejo de residuos sólidos y su relación con la actitud ambiental en niños de la comunidad nativa Amazonas, Nauta, 2019 - Alegría Torres, Béning (2021)
The investigation has like purpose show the relation that exists between the handle of solid waste and the environmental attitude in boys of the Native Community Amazons, the methodology considers the type of investigation applied, quantitative, no experimental. To estimate the confiabilidad of the instrument aplicor the alpha of Cronbach, used the descriptive statistics, as well as the statistical inferencial no parametric using the statistician CHI2, whose results are: of a total of 28 respondents, 04 boys had a level of knowledge very well (18-20 points), equivalent to the 17.9 %, 15 boys with a level of good knowledge (14-16 points) equivalent to 53.6%,04 boys had a level of regular knowledge (10-12 points) equivalent equally to 14.3% and 04 boys had a level of low knowledge (0-8 points) the same to 2.9%, noticing clearly that the level of knowledge of the boys polled finds concentrated mostly in well respectively. Besides, that, of 28 boys polled, 12 equivalents to the 42.9% had a VERY FAVOURABLE ATTITUDE and 15 equivalent to 53.6% had a FAVOURABLE ATTITUDE, only a boy showed a neutral attitude noticing clearly the predominancia of a FAVOURABLE and VERY FAVOURABLE ATTITUDE in the boys regarding the attitude to the environmental conservation. Concluye that, the value of the statistician CHI2 calculated is equal to 9.367, as well as a value of the significancia asymptotic is equal to 0.041, value that when being slightly lower to the level of significancia used (error type I 0.05), refuses the hypothesis posed, in where it concludes that it exists significant relation between both categorical variables to a level of confidence of 95%. The error to refuse the hypothesis of work is of 4.1% is slightly underneath of the permissible maximum error established in case to want to refuse the invalid hypothesis being true 5%